ANALYSIS OF COST AND TIME PERFORMANCE IN THE WADUNGASRI MARKET CHANNEL NORMALIZATION WORK IN SIDOARJO USING THE EARNED VALUE METHOD - Proboretno, Wuri; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
The construction project management for Wadungasri Sidoarjo Market Drainage Normalization aims to achieve cost, quality, and time objectives within a 100-day timeframe. This study addresses a 7.44% delay experienced by contractors, seeking to establish early warning mechanisms for poor project performance. The Earned Value Method is employed, integrating time and cost value concepts. Key indicators such as Cost Variance (CV), Schedule Variance (SV), work productivity index (CPI), time productivity index (SPI), project completion cost forecast (EAC), and project completion schedule forecast (ECD) are utilized. The results reveal a required cost of Rp 563,044,547.85 (ETC) and a 65-day timeframe (ETS) at the end of the 7th week, with a 0.64% increase in project completion cost (EAC) over the contract cost. The project completion time (EAS) is estimated at 114 days, reflecting a 0.14% extension. The analysis emphasizes the importance for construction service providers to implement efficient methods and consistent supervision to avoid delays in the Wadungasri Sidoarjo Market Drainage Normalization project.